The Influence of Pubertal Development on Adolescent Depression: The Mediating Effects of Negative Physical Self and Interpersonal Stress - Jiang, Lijiao; Yang, Dandan; Li, Yitong; Yuan, Jiajin (Frontiers in Psychiatry, 2021)
The current study examined the influence of pubertal development stage on depression and its psychosocial mechanisms in a nonclinical population of 502 adolescents (244 boys and 258 girls), graded 5 to 8. Results indicated that (1) pubertal development was positively correlated with depression, negative physical self and interpersonal stress. (2) There was a significant gender by pubertal development interaction on the measure of academic self-concept, which is accounted for by decreased academic self in boys but not in girls as a function of pubertal development. (3) Mediation analyses showed that increased depression in late compared to pre- puberty is partly mediated by the enhancement of negative physical self and interpersonal stress. These findings suggest that the late stage of puberty is coupled by a higher risk of depression in adolescents partly through increased negative physical self and interpersonal stress.